Letter: vedolizumab for the management of inflammatory bowel disease in patients after liver transplantation for primary sclerosing cholangitis. Issue 2 (8th December 2016) - Hartery, K.; O'Reilly, S.; Houlihan, D.; Doherty, G.; Mulcahy, H.; Cullen, G.; Sheridan, J.
Abstract : Linked Content This article is linked to Stallmach et al paper. To view this article visit https://doi.org/10.1111/apt.13813 .